الالتزام القانوني بالإفصاح في سوق الأوراق المالية وفقاً للتشريع السوري (مفهومه وأنواعه) - قرباش محمد; القوصي همام (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يدرس هذا البحث موضوع الالتزام القانوني بالإفصاح عن المعلومات الجوهرية المؤثِّرة في سوق الأوراق المالية, والتي تعطي المتعامل في السوق إمكانية اتخاذ قراره الاستثماري. حيث إنَّ المشرع يريد أن يتَّخذ المستثمر قراره على بيِّنة ودراسة للمركز المالي الحقيقي المتعلِّق بمُصدر الأوراق المالية, وأن لا يتم التغرير به, وخداعه بمعلومات مُضلِّلة, ولذلك قام المشرع بإقرار الالتزام القانوني بالإفصاح عن المعلومات التي تهم المستثمرين, ووضعه على عاتق جميع مُصدري الأوراق المالية المُدرجين في السوق. ولذلك, سوف نقوم بدراسة هذا الالتزام القانوني بالإفصاح, من حيث مفهومه العام, وتفصيلاته, كما ندرس أنواعه وذلك من وجهة نظر المشرع السوري, ومدى توفيقه بوضع هذه القواعد القانونية, لنصل في النهاية إلى مجموعة من النتائج والتوصيات. ومن أهم الاستنتاجات التي توصَّلنا إليها: تعريف قانوني خاص بالإفصاح, وضرورة اشتراط صفة التأثير على معلومات الإفصاح, وإقرار إلزامية الإفصاح الربع سنوي, واستخدام الوسائل الإلكترونية فيما يتعلَّق بالإفصاح الفوري الطارئ, وأنَّ الإفصاح كالتزام قانوني أكثر صرامة من الشفافية. وقد تمَّ إجراء البحث في مدينة حلب, واستغرق شهراً لإعداده. This research examines the subject of the legal obligation to disclose material affecting information on the securities exchange, and which gives the ability to the trader at the market to take his investment decision. That is, the legislator wants the trader to take his decision on aware of a study of the financial position on the issuer of securities, and not be seduced by, and misled with false information, and for that reason the legislator issue an obligation to disclose all material information which makes a difference for investors. Therefore, we will study the legal obligation to disclose, in terms of common sense, and its specificity, as we study different forms from the perspective of Syrian law, and how to the extent of successfulness of making this legal rules, and finally reach to a set of conclusions and recommendations. One of the main conclusions we reached is the following: a legal definition of disclosure, the necessity of conditioning the effect of the disclosure information, the adoption of obligatory disclosure of quarterly, the use of electronic means with the immediate disclosure, and that the disclosure as a legal obligation is more stringent than the transparency. The research was conducted in the city of Aleppo, and it took months to prepare.